Nuevos textos y renovados pretextos - Salles, Vania; Mc Phail Fanger, Elsie (Colegio de México, Programa Interdisciplinario de Estudios de la Mujer, 1994)
"Broad-based collection of 19 papers focuses on presence and participation of women in Mexican society, including rural women's issues, urban women's work, health, sociodemographic aspects of women's work, family organization, power and political participation, and religion and kinship. Of special interest are Roberto Campos Navarro's paper on curanderismo and Rosa Aurora Espinosa Gómez's case study of expressions of power in Apaseo el Alto, Guanajuato, during late 1970s"--Handbook of Latin American Studies, v. 57.